Claves para la educación del siglo XXI - Bermeo Ramírez, Carmen Rosa (2014)
This paper presents first the predominant feature of the century, which is thepermanent change of sustained and irreversible. The change that has impactedall aspects of human life, with consequences that are affecting all social systems,in its broadest sense. It is easy to deduce that the most significant impact is ineducation, finger on it depends the development, stagnation of societies aroundthe world.New proposals for teaching and learning, under new conditions must berecognized and taken to ensure that the change is the best friend of man in hissearch for a better quality of life.